2000
DOI: 10.1093/brain/123.11.2321
|View full text |Cite
|
Sign up to set email alerts
|

The peripheral benzodiazepine binding site in the brain in multiple sclerosis

Abstract: This study identifies by microautoradiography activated microglia/macrophages as the main cell type expressing the peripheral benzodiazepine binding site (PBBS) at sites of active CNS pathology. Quantitative measurements of PBBS expression in vivo obtained by PET and [(11)C](R)-PK11195 are shown to correspond to animal experimental and human post-mortem data on the distribution pattern of activated microglia in inflammatory brain disease. Film autoradiography with [(3)H](R)-PK11195, a specific ligand for the P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
201
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 598 publications
(212 citation statements)
references
References 50 publications
11
201
0
Order By: Relevance
“…This study extends earlier observations using [ 3 H](R)-PK11195 (Banati et al, 2000) in which increased binding in the spinal cords from rats with tEAE, at peak of clinical disease was documented.…”
Section: Autoradiography and Immunochemistry Correlation With The Uprsupporting
confidence: 90%
See 1 more Smart Citation
“…This study extends earlier observations using [ 3 H](R)-PK11195 (Banati et al, 2000) in which increased binding in the spinal cords from rats with tEAE, at peak of clinical disease was documented.…”
Section: Autoradiography and Immunochemistry Correlation With The Uprsupporting
confidence: 90%
“…A study on the same model (Banati et al, 2000) also found normal autoradiography up to day 4 with [3H]-PK11195. One should point out that we used two appropriate controls (not only naive rats).…”
Section: Autoradiography and Immunochemistry Correlation With The Uprmentioning
confidence: 66%
“…The synthesis of selective ligands for the PBR is therefore invaluable not only in characterising the receptor but also since the PBR could itself be a worthwhile target for therapeutic intervention. PK 11195 has been used in countless activated microglia studies and has provided a number of novel insights on the cellular pathology involved in certain disease states including MS [52] and AD [53]. Consequently, PK 11195 has been tagged the gold standard of PBR ligands.…”
Section: Benzothiazepinesmentioning
confidence: 99%
“…Increased levels of TSPO in the CNS was originally considered to be specific for activated microglia as well as infiltrating macrophages, representing a neuroinflammatory biomarker, although it has since been established that TSPO expression is also increased in reactive astrocytes [22]. increased TSPO expression in a range of neuroinflammatory and neurodegenerative conditions, including Rasmussen's encephalitis [18], herpes encephalitis [19], multiple sclerosis [20], TBI [21], stroke [22] and Alzheimer's disease [23] (for detailed reviews see [7,13]). In the healthy human brain, [ 11 C]PK11195 uptake is low, with relatively high binding in subcortical structures, including midbrain, thalamus and basal ganglia, with overall brain uptake increasing with age [24].…”
Section: Tspo As a Target For Pet Imagingmentioning
confidence: 99%